Complete Response of Pazopanib Treatment in Cystic Renal Cell Carcinoma with Liver Metastasis Patient: A Case Report - Muhammad Firas Balafif; Kurnia Penta Seputra; Medianto Medianto (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Cystic renal cell carcinoma (CRCC) is a rare renal malignancy. Complete radiologic response of metastatic CRCC with liver metastasis following pazopanib therapy is rarely reported. This case highlights a successful treatment outcome. Objective: To describe the clinical course, diagnostic workup, treatment strategy, and complete radiologic response in a patient with cystic renal cell carcinoma (CRCC) presenting with liver metastasis and treated with pazopanib. Methods: This case report describes a single patient diagnosed with cystic renal cell carcinoma with hepatic metastasis. Clinical, laboratory, imaging, including computed tomography (CT) and magnetic resonance imaging (MRI), and histopathologic data were collected and analyzed. The CARE guidelines for case report writing were followed. Results: A 50-year-old woman presented with a 3-month history of weakness, decreased appetite, weight loss, and persistent anemia (Hb 8 g/dL) that was unresponsive to blood transfusion. Imaging studies revealed a large left cystic renal mass measuring 13.6 × 11.8 × 11 cm, with suspected liver metastasis in segment VIII. Following cytoreductive nephrectomy, histopathologic examination confirmed papillary renal cell carcinoma, Fuhrman grade 2, leading to a diagnosis of cystic renal cell carcinoma with hepatic metastasis. The patient subsequently received pazopanib 400 mg twice daily. After 10 months of treatment, complete radiologic disappearance of the liver metastasis was achieved. Conclusion: This case demonstrates that pazopanib therapy, in combination with cytoreductive nephrectomy, can achieve a complete radiologic response of hepatic metastasis in CRCC. Pazopanib represents a viable and well-tolerated targeted therapy option for metastatic CRCC, warranting further clinical investigation.